The infestation of Cylas formicarius (Fabricius) (Coleoptera: Brentidae) and its effect on postharvest quality of storage sweet potatoes - Nur Aida Hashim,; Nurul Adawiyah Zulkifli,; Khadijah Saad,; Norasmah Basari, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Sweet potato is an important cash crop in Malaysia. The production and storage of sweet potato is facing huge problem from weevil, Cylas formicarius infestation. The attack of this weevil has caused massive losses due to reduction in sweet potato quality and consequently marketability. Therefore, this study was conducted to determine the number of sweet potato weevil (SPW) emerged from infested sweet potatoes and the post-harvest parameters of sweet potatoes when infested by the weevil. The healthy and damaged sweet potatoes were purchased from roadside stalls at Pengkalan Kubur, Besut, Terengganu. A mean of 361.0 ± 135.57 weevils emerged from two kilograms of damaged sweet potatoes throughout 66 days of observation. There was no significant difference between male and female weevils emergence (p > 0.05). The sex ratio male to female is 1:1.2. The post-harvest parameters of weevil infested and not-infested (control) sweet potato were not significantly difference in regards of total soluble solid (TSS) and pH value. Similarly, the total anthocyanin in purple sweet potato and total carotenoid in orange sweet potato also had no significant different between infested and control. Significant difference was observed in percentage of weight loss between weevil infested and control groups.